Serving some and serving all: how providers navigate the challenges of providing racially targeted health services. Issue 5 (3rd September 2017) - Zhou, Amy
ABSTRACT: Objectives: Racially targeted healthcare provides racial minorities with culturally and linguistically appropriate health services. This mandate, however, can conflict with the professional obligation of healthcare providers to serve patients based on their health needs. The dilemma between serving a particular population and serving all is heightened when the patients seeking care are racially diverse. This study examines how providers in a multi-racial context decide whom to include or exclude from health programs. Design: This study draws on 12 months of ethnographic fieldwork at an Asian-specific HIV organization. Fieldwork included participant observation of HIV support groups, community outreach programs, and substance abuse recovery groups, as well as interviews with providers and clients. Results: Providers managed the dilemma in different ways. While some programs in the organization focused on an Asian clientele, others de-emphasized race and served a predominantly Latino and African American clientele. Organizational structures shaped whether services were delivered according to racial categories. When funders examined client documents, providers prioritized finding Asian clients so that their documents reflected program goals to serve the Asian population. In contrast, when funders used qualitative methods, providers could construct an image of a program that targets Asians during evaluations while they included other racial minorities in their everyday practice. Program services were organized more broadly by health needs. Conclusion: Even within racially targeted programs, the meaning of race fluctuates and is contested. Patients' health needs cross cut racial boundaries, and in some circumstances, the boundaries of inclusion can expand beyond specific racial categories to include racial minorities and underserved populations more generally.